Sound - Attali, Jacques; Celant, Germano; Chion, Michel; Kelly, Caleb, 1972- (London : Whitechapel Gallery, 2011)
Abramovic Marina; Vito Acconci; Doug Aitkin; Maryanne Amacher; Laurie Anderson; John Cage; Kim Cascone; Martin Creed; Philip Dadson; Paul Demarinis; Bill Fontana; Kim Gordon; Dan Graham; Joyce Hinterding; Rebecca Horn; Ryoji Ikeda; Mike Kelley; Christina Kubish; Bernhard Leitner; Alvin Lucier; Len Lye; Christian Marclay; Robert Morris; Max Neuhaus; Carsten Nicolai. Herman Nitch; Yoko Ono; Nam June Paik; Luigi Russolo; Karin Sander; Mieko Shiomi
Formerly CIP.
boek
Keywords: Sound in art; Arts, Modern -- 20th century; Arts, Modern -- 21st century